2002
DOI: 10.1081/ese-120013269
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Leaking Gases by Op-Ftir Remote Sensing

Abstract: Measurement of leaking gases using Open Path Fourier Transform Infrared (OP-FTIR) spectroscopy was carried out in this study to acquire Path Integrated Concentration (PIC) data. Three hazardous Volatile Organic Compounds (VOCs) namely methylene chloride, chloroform and acetone were analyzed. For the two-component leaking source, the PIC data were easily obtained through ordinary calculation and compared to those obtained from Artificial Neural Network (ANN). When the leaking source was composed of three VOCs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Lechner et al (2001) also reported positive interference when developing a method to discriminate compounds which absorb in similar spectral regions, finding difficulty differentiating between different alcohols, acetates and methyl-alkanes in air from the production hall of a recycling centre. Such analyses ostensibly require more complex analytical methods to incorporate spectral correction that allows for interference (Li et al, 2002). Consequently, the infrared spectra in this study were reanalysed using a PLS method as this is considered to be more effective for complex mixtures (Stuart, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Lechner et al (2001) also reported positive interference when developing a method to discriminate compounds which absorb in similar spectral regions, finding difficulty differentiating between different alcohols, acetates and methyl-alkanes in air from the production hall of a recycling centre. Such analyses ostensibly require more complex analytical methods to incorporate spectral correction that allows for interference (Li et al, 2002). Consequently, the infrared spectra in this study were reanalysed using a PLS method as this is considered to be more effective for complex mixtures (Stuart, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Infrared spectroscopy is an effective tool for analyzing unknown gases and has been widely used in qualitative and quantitative measurements of automobile exhaust (Sebih et al, 2010;White et al, 2011;Yamamoto et al, 2011), harmful gas leaks (Harig et al, 2005(Harig et al, , 2007Li et al, 2002) and greenhouse gas emissions (Gardiner et al, 2008;Geibel et al, 2010;TsanChang et al, 2000), among other applications. Compared with GC-MS and many other laboratory analytical methods, infrared spectroscopy is more flexible and can realize non-destructive, real-time and continuous tests as well as remote-sensing measurements (Bacsik et al, 2006;Marshall et al, 1994;Ross & Todd, 2002).…”
Section: Introductionmentioning
confidence: 98%
“…Chromatographic methods were often used to detect acetone in conventional analytic techniques [5]. Other reported techniques include FTIR spectroscopy [6] and ion mobility spectrometry [7], which typically needed complicated apparatus, with the sample being pre-treated for a long time, and the response was fairly sluggish. The recent development of fluorescent sensors, whose basis was often on metal-organic frameworks (MOF) or coordination polymers (CPS), also aimed to detect acetone.…”
Section: Introductionmentioning
confidence: 99%